Teachers Have Problems Teaching Early Children During the Covid-19 Pandemic - Nuryati Nuryati; Yonia Ilma Insyira; Uyu Muawanah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Study this aim for know teacher problems in teaching PAUD during the Covid-19 pandemic in the District Attack, and for know effort made _ in overcome Thing that. The subject study is a PAUD teacher in the district Attack consisting of 126 respondents from 108 PAUD institutions in the district Attack. Method research used _ is descriptive quantitative with survey technique, researcher To do Interview with spread questionnaire online to _ respondents. The evaluation questionnaire uses the Guttman scale. Research results show that 65% of the total PAUD ( Similar Education Units ) in the district attacked show many problems faced by PAUD teachers while teaching, especially during the pandemic surveyed all PAUD teachers in Serang. The later district from survey results show same result and opinion _ that is demands from parents _ for implemented system offline learning or stare face; so that learning more effective and optimal.